Related-key rectangle attack on the full ARIRANG encryption mode - ZHANG Peng1; LI Rui-lin1; LI Chao1 (Tongxin xuebao)
The security of the block cipher used in the compression function of ARIRANG,which was one of the SHA-3 candidates,was revaluated.Based on a linear transformation of the master key and the all-one differential of the round function,a full 40-round related-key rectangle attack of the ARIRANG encryption mode was presented,which was the first cryptanalytic result of the ARIRANG encryption mode.The result shows that the ARIRANG encryption mode as a block cipher is not immune to the related-key rectangle attack.